The future of coworking spaces in Cebu a scenario-driven technology foresight - Jain, Charisse Ann D.; Imbang, Glen A. (Quezon City University of the Philippines Diliman, 2022)
The Covid-19 pandemic, the digital transformation of the modern world and the proliferation of the gig economy have brought significant changes in the business landscape, prompting to the rise in popularity of coworking spaces. To investigate the future of the coworking space industry, the study focused on Metro Cebu, identified as one of the top earners among independent contractors.

Using scenario building methodology and conducting interview with local experts who had firsthand experience as coworking space customers or operators, the study explored the potential future developments. The analysis yielded valuable insights into the potential benefits that technological advancements, government support and other studies could offer to small enterprises in the region. Potential avenues for future investigation included strategic alliances, collaborations and joint ventures beyond Metro Cebu. Additionally, a technology road mapping method enabled a comprehensive analysis of the coworking space market.

By examining the future of the coworking space business in Metro Cebu, the study provides valuable insights to stakeholders, legislators, and entrepreneurs, aiding them in their decision-making processes.

Furthermore, the study analysis supports the notion that coworking spaces have been a disruptive force in the way people work and have served as a complementary alternative to traditional offices in the region.
Thesis
Keywords: Work environment